2006
DOI: 10.1037/0735-7044.120.2.313
|View full text |Cite
|
Sign up to set email alerts
|

Opioid receptors in the midbrain periaqueductal gray regulate prediction errors during Pavlovian fear conditioning.

Abstract: The authors used a within-subject blocking design to study the role of ventrolateral periaqueductal gray (v1PAG) opioid receptors in regulating prediction errors during Pavlovian fear conditioning. In Stage I, the authors trained rats to fear conditioned stimulus (CS) A by pairing it with shock. In Stage II, CSA and CSB were co-presented and followed with shock. Two novel stimuli, CSC and CSD, were also co-presented and followed with shock in Stage II. CSA blocked fear from accruing to CSB. Blocking was preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
88
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 44 publications
8
88
0
Order By: Relevance
“…80,210,219 This effect, like the retardation of extinction, is mimicked by infusion of naloxone or the m opioid antagonist CTAP directly into vlPAG. 80 The second additional phenomenon examined by McNally and co-workers is overexpectation, in which two CSs, C and D, are paired with the US separately in one phase of training, then are paired with the US in compound in a second phase (lower panel of Figure 4). Despite 100% reinforcement of C and D throughout the experiment, both CSs are observed to elicit less fear at the conclusion of phase 2 than they did at the conclusion of phase 1.…”
Section: Neurotransmitter Systemsmentioning
confidence: 98%
See 1 more Smart Citation
“…80,210,219 This effect, like the retardation of extinction, is mimicked by infusion of naloxone or the m opioid antagonist CTAP directly into vlPAG. 80 The second additional phenomenon examined by McNally and co-workers is overexpectation, in which two CSs, C and D, are paired with the US separately in one phase of training, then are paired with the US in compound in a second phase (lower panel of Figure 4). Despite 100% reinforcement of C and D throughout the experiment, both CSs are observed to elicit less fear at the conclusion of phase 2 than they did at the conclusion of phase 1.…”
Section: Neurotransmitter Systemsmentioning
confidence: 98%
“…Brain structures Several brain structures have been implicated in fear extinction and fear inhibition more generally, including sensory cortex, [74][75][76][77][78] periaqueductal gray [79][80][81] (see below), inferior colliculus, 82 lateral septum, [83][84][85][86] bed nucleus of the stria terminalis, 87 and ventral 88 and dorsal striatum. 89 In this section, we will focus on those for which there is the most information available: the amygdala, hippocampus and prefrontal cortex.…”
Section: Neural Mechanismsmentioning
confidence: 99%
“…Previous studies have shown that systemic administrations of naloxone prevent the blocking of conditioned fear (Fanselow and Bolles 1979;Matzel et al 1988;McNally et al 2004a;McNally and Cole 2006). However, these studies have focused on multi-trial blocking.…”
Section: Experiments 3: Effects Of Naloxone On One-trial Blocking Of Fmentioning
confidence: 97%
“…A CS which is a better predictor of the outcome will command more attention and consequently be better learned about than a CS which is a poorer predictor and which is consequently ignored. McNally and Cole (2006) demonstrated that vlPAG µ-opioid receptors contribute to predictive fear learning. However, the design of those experiments did not permit examination of whether this µ-opioid receptor contribution to predictive fear learning was direct and achieved via alterations in US processing or indirect and achieved via alterations in CS processing.…”
mentioning
confidence: 99%
See 1 more Smart Citation